1995
DOI: 10.1073/pnas.92.22.10436
|View full text |Cite
|
Sign up to set email alerts
|

Lack of functional retinoblastoma protein mediates increased resistance to antimetabolites in human sarcoma cell lines.

Abstract: Growth inhibition assays indicated that the IC50 values for methotrexate (MTX) and 5-fluorodeoxyuridine (FdUrd) in HS-18, a liposarcoma cell line lacking retinoblastoma protein (pRB), and SaOS-2, an osteosarcoma cell line with a truncated and nonfunctional pRB, were 10-to 12-fold and 4-to 11-fold higher, respectively, than for the HT-1080 (fibrosarcoma) cell line, which has wild-type pRB. These Rb-/-cell lines exhibited a 2-to 4-fold increase in both dihydrofolate reductase (DHFR) and thymidylate synthase (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 54 publications
3
55
0
Order By: Relevance
“…However, the basal expression of EGFR and TS was also assessed in this study to evaluate the effect of 72-h treatment with IC 50 levels of erlotinib, pemetrexed, and their combination in all cell lines. Because previous studies have shown a strong correlation between expression levels of TS and its upstream transcriptional regulator E2F-1 (Li et al, 1995;Huang et al, 2007), and because other studies showed that EGFR-TKIs affected E2F-1 (Kobayashi et al, 2006;Suenaga et al, 2006), we also evaluated the expression of E2F-1 mRNA. Moreover we studied the expression levels of DHFR, GARFT, RFC, ␥-glutamyl hydrolase (␥GH), and folyl-polyglutamate synthetase (FPGS).…”
Section: Erlotinib and Pemetrexed In Nsclc 1291mentioning
confidence: 99%
“…However, the basal expression of EGFR and TS was also assessed in this study to evaluate the effect of 72-h treatment with IC 50 levels of erlotinib, pemetrexed, and their combination in all cell lines. Because previous studies have shown a strong correlation between expression levels of TS and its upstream transcriptional regulator E2F-1 (Li et al, 1995;Huang et al, 2007), and because other studies showed that EGFR-TKIs affected E2F-1 (Kobayashi et al, 2006;Suenaga et al, 2006), we also evaluated the expression of E2F-1 mRNA. Moreover we studied the expression levels of DHFR, GARFT, RFC, ␥-glutamyl hydrolase (␥GH), and folyl-polyglutamate synthetase (FPGS).…”
Section: Erlotinib and Pemetrexed In Nsclc 1291mentioning
confidence: 99%
“…Lack of functional Rb protein appears to mediate increased resistance to antimetabolites in human sarcoma cell lines (Li et al, 1995).…”
Section: Sarcomasmentioning
confidence: 99%
“…This is attributed to elevated levels of the metabolic enzymes targeted by these compounds (TS, dihydrofolate reductase and ribonucleotide reductase (RNR)) Li et al, 1995;Angus et al, 2002). Therefore, we next probed the consequences of acute RB loss on the response of primary and immortal cultures to antimetabolites.…”
Section: Disparate Rb-dependent Checkpoint Responses Of Primary and Imentioning
confidence: 99%
“…However, TS inhibition is believed to be the principle mechanism of action of 5-FU (Peters et al, 2002). TS is a well established target of the RB/E2F signaling axis DeGregori et al, 1995;Li et al, 1995), and RB-deficient cell lines display increased TS expression and activity that is associated with resistance to agents that target TS . Therefore, we next sought to determine the effects of acute RB loss on TS expression in primary MAFs and how this contributes to the observed lack of cell cycle checkpoint response to 5-FU in RB-deficient MAFs.…”
Section: Disparate Rb-dependent Checkpoint Responses Of Primary and Imentioning
confidence: 99%